Ethylene-regulated reactive oxygen species and nitric oxide under salt stress in tomato cell suspension culture - Poór, Péter; Tari, Irma (Acta Biologica Szegediensis, 2011)
In the present work the role of ethylene (ET) in the accumulation of reactive oxygen species (ROS) and nitric oxide (NO) was investigated under the effect of sublethal (100 mM) and lethal (250 mM) concentrations of NaCl in tomato cell suspension culture. In these cultures the salt stress increased the production of ET and ROS after 6 hours but NO level was enhanced only at 100 mM NaCl. This corresponded with the lower ratio of dead cells (20%) in these samples suggesting that NO functioned as a protecting compound under moderate salt stress. The synthesis of ET was further enhanced by the addition of ET precursor, 1-aminocyclopropane-1-carboxylic acid (ACC), which increased the ROS production under both moderate and severe salt stress. However, NO levels decreased in the presence of ACC in cells exposed to 100 mM NaCl and did not change after treatment with 250 mM NaCl. The effect of ET on ROS production induced by salt stress could be blocked by silver thiosulphate (STS), an inhibitor of ET action. In accordance with the decreased ROS production STS reduced the death of cells in the presence of 250 mM NaCl. In the presence of ACC the enhanced ROS production concurrently with low NO levels led to the increased cell death after 100 mM NaCl treatment. These results show that the cell viability is determined by the ET generated ROS and NO ratio under salt stress.